An empirical model for determining the radial force–deflection characteristics of off–road bicycle tyres. (4th August 2014) - Moore, D.F.; Wang, E.L.; Hull, M.L.
To characterize tyre stiffness on uneven terrain for use in a mathematical model of an off–road bicycle, this study developed an empirical model of tyre radial load–deflection behaviour. To provide data for the tyre model, load–deflection was measured for a single tyre compressed on a variety of semicircular surfaces spanning radii 58.4 cm convex to 58.4 cm concave. A power equation which included two independent data for both concave and convex surfaces - tyre deflection and surface radius - and six coefficients was found to fit the experimental data for both surfaces. However, the coefficients were dependent on the type of surface (i.e. either convex or concave). The concave surface model predicted the force to within a maximum relative error of 4.2% for all concave surfaces tested while the maximum relative error for the convex surfaces was bounded by 13.5%. With the accuracy of the tyre model established, it can now be incorporated into a bicycle/rider system model.